Testing the Social Justice Goals of Education: a Role for Anti-Discrimination Law - de Plevitz, Loretta (The Australian Journal of Indigenous Education, 2007)
Abstract Policy documents on Indigenous education include statements such as equitable access to education, participation and outcomes that can be broadly described as social justice goals. However, there has been little academic analysis of how these goals are to be achieved. This paper proposes that the indirect discrimination provisions in Australian anti-discrimination law can provide a framework in which the goals can be evaluated against the endemic effects of dominant power on mainstream education. The legal provisions are designed to assess whether a policy or practice might adversely affect certain groups in our society distinguished by, for example, their “race”. If a higher proportion of persons who do not have that particular attribute can comply with the policy or practice, and the demand is unreasonable in the circumstances, then this will constitute unlawful indirect discrimination. This paper analyses three social justice strategies which appear to be race-neutral and to apply equally to all students, Indigenous and non-Indigenous: Indigenous studies in the curriculum, using Standard English in the classroom, and instilling Australian values. The outcome suggests that these approaches may have an adverse impact on Indigenous students, and may even be undermining the social justice goals they set out to deliver.